Candida tropicalis spondylitis in a non-tropical immunocompetent patient: a case report and review of the literature - Yang, Hong; Wang, Xin; Zhu, Weijian; Zhou, Bei (Frontiers in Medicine, 2025)
BackgroundTropical Candida spondylitis is an uncommon cause of lower back pain in patients, especially in non-tropical areas or in patients not at risk of immunocompromise.Case presentationA 65-year-old woman presented with a six-month history of poorly managed low back pain, now accompanied by numbness and pain in both lower extremities. Her medical history was significant for tertiary hypertension. Inflammatory markers were mildly elevated. MRI fluid sequences revealed lamellar enhancement of the L4-5 vertebral bodies, narrowing of the intervertebral space, peripheral soft tissue edema, and spinal canal compression. After 3 weeks of empirical anti-tuberculosis therapy, the patient’s symptoms did not improve, prompting posterior lesion debridement and autologous iliac bone grafting with pedicle screw fixation. Postoperatively, disc tissue cultures and next-generation sequencing (NGS) identified Candida tropicalis. The patient was subsequently treated with a six-week course of voriconazole, resulting in symptomatic improvement, with no recurrence observed during follow-up.ConclusionThe imaging and clinical presentation of Candida tropicalis spondylitis can closely mimic that of tuberculous spondylitis, particularly in patients without clear risk factors for immune compromise. This overlap in presentation often complicates the differential diagnosis, leading to potential delays in appropriate treatment.